Power without law : the Supreme Court of Canada, the Marshall decisions, and the failure of judicial activism - Cameron, Alex M. (McGill-Queen's University Press, 2009)
The Supreme Court of Canada decision in the Marshall case asserted sweeping Native treaty rights and generated intense controversy.